Exchange factor EFA6R requires C-terminal targeting to the plasma membrane to promote cytoskeletal rearrangement through the activation of ARF6 - Venkat Kanamarlapudi (Journal of Biological Chemistry, 2014)
ADP-ribosylation factor 6 (ARF6) small GTPase regulates membrane trafficking and cytoskeleton rearrangements at the plasma membrane (PM) by cycling between the GTP-bound active and GDP-bound inactive conformations. Guanine nucleotide exchange factors (GEFs) activate ARF6. The exchange factor for ARF6 (EFA6) R has been identified as a biomarker for ovarian cancer. EFA6R shares the catalytic Sec7, pleckstrin homology (PH), and coiled coil (CC) domains of the other EFA6 family GEFs. Here we report the functional characterization of EFA6R. Endogenous EFA6R was present in the plasma membrane fraction. The exogenously expressed FLAG- and GFP-tagged EFA6R were targeted to the PM. In vitro, GFP-EFA6R associated weakly but preferentially with phosphatidylinositol 4,5-bisphosphate (PIP2) through the PH domain. EFA6R required both its PH and CC domains localized at the C terminus to target the PM. Consistent with this, EFA6R lacking the CC domain (EFA6R deltaCC) was released from the PM into the cytosol upon PIP2 depletion, whereas EFA6R release from the PM required both PIP2 depletion and actin destabilization. These results suggest that the dual targeting via the PH and CC domains is important for the PM localization of EFA6R. EFA6R specifically catalyzed the GTP loading of ARF6 in mammalian cells. Moreover, EFA6R regulated ARF6 localization and thereby actin stress fiber loss. The GEF activity of EFA6R was dependent on the presence of the Sec7 domain. The PH and CC domains were also required for the in vivo GEF activity of EFA6R but could be functionally replaced by the CAAX motif of K-Ras, suggesting a role for these domains in the membrane targeting of EFA6R.